External Risk Factors Influence on the Financial Stability of Construction Companies - Kapustina, N.V.; Rjachovskaya, A.N.; Rjachovskij, D.I.; Gantseva, L.V. (Journal of Reviews on Global Economics, 2018)
The modern conditions of construction companies’ activities in Russia are influenced by various processes: developing globalization, limitation of free trade due to economic sanctions, man-made disasters growth, worldwide digitalization, constantly evolving technologies. The purpose of this study is to develop a model for assessing risk factors’ impact on the financial stability of construction companies using regression analysis based on dependencies between risk factors and financial stability of construction companies on the basis of statistical data over the past 10 years. The following methods were used: questioning of owners and key employees in construction companies on the indicators choice that characterize external risk factors, correlation analysis, regression analysis, expert evaluation method, trend line method. As a result it was revealed that in order to create favorable conditions for the construction companies’ growth, a stable legislative base, a stable ruble rate and an activation of investments in fixed assets are needed. The proposed tool for assessing external risk factors and their impact on the construction companies’ financial sustainability can be used both to assess the organization’s environment and to assess various risk situations in order to further use the results in decision-making.